Pelatihan Pengembangan Potensi dan Menciptakan Ketahanan Pangan Masyarakat Desa Ngargosari - Dewi Ismoyowati (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this Village Thematic Community Service Program is to help and provide solutions to the problems faced by the community as well as to provide real work experience in the field to apply the knowledge gained during college to the community. The thematic KKN-Thematic to build this village has been carried out in Ngargosari Village, Sumber Lawang District, Sragen Regency. Several program activities that have been implemented are models for developing local potential to improve the standard of living of the local community. Activities carried out include Socialization and Training on Maggot Cultivation, Vegetable Cultivation Training with the Floating Raft Hydroponic Method, Vegetable Crop Cultivation Training with Polybag Media, Socialization on Ecosystem Conservation and Fish Seed Release in Kedungombo Reservoir. The method used is empowering the target group including learning techniques in the form of providing theory and simulation to the target community and then direct practice with students and the community so that it provides enormous benefits in food security for villagers.